Effects of a Post-Shock Injection of the Kappa Opioid Receptor Antagonist Norbinaltorphimine (norBNI) on Fear and Anxiety in Rats - Rogala, Benjamin; Li, Yonghui; Li, Sa; Chen, Xiaoyu; Kirouac, Gilbert J. (PLOS ONE, 2012)
Exposure of rats to footshocks leads to an enduring behavioral state involving generalized fear responses and avoidance. Recent evidence suggests that the expression of negative emotional behaviors produced by a stressor is in part mediated by dynorphin and its main receptor, the kappa opioid receptor (KOR). The purpose of this study was to determine if a subcutaneous injection of the long-acting KOR antagonist norbinaltorphimine (norBNI; 15.0 and 30.0 mg/kg) given 2 days after an acute exposure of rats to footshooks (5×2 s episodes of 1.5 mA delivered over 5 min) attenuates the expression of lasting fear and anxiety. We report that exposure of rats to acute footshock produced long-lasting (>4 weeks) fear (freezing) and anxiety (avoidance of an open area in the defensive withdrawal test). The 30 mg dose of norBNI attenuated the fear expressed when shock rats were placed in the shock context at Day 9 but not Day 27 post-shock. The same dose of norBNI had no effect on the expression of generalized fear produced when shock rats were placed in a novel chamber at Days 8 and 24. In contrast, the 30 mg dose of norBNI produced consistent anxiolytic effects in shock and nonshock rats. First, the 30 mg dose was found to decrease the latency to enter the open field in the defensive withdrawal test done 30 days after the shock exposure. Second, the same high dose also had anxiolytic effects in both nonshock and shock rats as evidence by a decrease in the mean time spent in the withdrawal box. The present study shows that systemic injection of the KOR antagonist norBNI had mixed effect on fear. In contrast, norBNI had an anxiolytic effect which included the attenuation of the enhanced avoidance of a novel area produced by a prior shock experience.